Pre-treatment non-target lung FDG-PET uptake predicts symptomatic radiation pneumonitis following Stereotactic Ablative Radiotherapy (SABR). Issue 3 (June 2016) - Chaudhuri, Aadel A.; Binkley, Michael S.; Rigdon, Joseph; Carter, Justin N.; Aggarwal, Sonya; Dudley, Sara A.; Qian, Yushen; Kumar, Kiran A.; Hara, Wendy Y.; Gensheimer, Michael; Nair, Viswam S.; Maxim, Peter G.; et al.
Abstract: Purpose: To determine if pre-treatment non-target lung FDG-PET uptake predicts for symptomatic radiation pneumonitis (RP) following lung stereotactic ablative radiotherapy (SABR). Methods: We reviewed a 258 patient database from our institution to identify 28 patients who experienced symptomatic (grade ⩾ 2) RP after SABR, and compared them to 57 controls who did not develop symptomatic RP. We compared clinical, dosimetric and functional imaging characteristics between the 2 cohorts including pre-treatment non-target lung FDG-PET uptake. Results: Median follow-up time was 26.9 months. Patients who experienced symptomatic RP had significantly higher non-target lung FDG-PET uptake as measured by mean SUV ( p  < 0.0001) than controls. ROC analysis for symptomatic RP revealed area under the curve (AUC) of 0.74, with sensitivity 82.1% and specificity 57.9% with cutoff mean non-target lung SUV > 0.56. Predictive value increased (AUC of 0.82) when mean non-target lung SUV was combined with mean lung dose (MLD). We developed a 0–2 point model using these 2 variables, 1 point each for SUV > 0.56 or MLD > 5.88 Gy equivalent dose in 2 Gy per fraction (EQD2), predictive for symptomatic RP in our cohort with hazard ratio 10.01 for score 2 versus 0 ( p  < 0.001). Conclusions: Patients with elevated pre-SABR non-target lung FDG-PET uptake are at increased risk of symptomatic RP after lung SABR. Our predictive model suggests patients with mean non-target lung SUV > 0.56 and MLD > 5.88 Gy EQD2 are at highest risk. Our predictive model should be validated in an external cohort before clinical implementation.